2020
DOI: 10.12688/f1000research.21297.1
|View full text |Cite
|
Sign up to set email alerts
|

4K ultra HD technology reduces operative time and intraoperative blood loss in colorectal laparoscopic surgery

Abstract: Background: HD systems are routinely used in laparoscopic surgery, 4K ultra HD monitors are mainly available within specialized, high-volume laparoscopic centers. The higher resolution of 4K ultra HD video could upgrade the surgical performance improving intraoperative and post-operative outcomes. Methods: We performed a retrospective comparative analysis of intraoperative parameters and post-operative outcomes in a cohort of patients operated on for elective laparoscopic procedures for colo-rectal cancer duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Relative lack of depth perception (2D view) has been a major disadvantage with laparoscopy compared to open surgery. To overcome this, 4K ultra high definition technology[ 35 ] and 3D laparoscopic technology have been introduced[ 36 ], and several trials have compared the two[ 35 , 37 ]. Neither seems superior to the other, and a recent consensus statement from the European Association of Endoscopic Surgeons concluded that further robust research is required to investigate the avantages of 3D laparoscopy system[ 38 ].…”
Section: Peri-operative Considerationsmentioning
confidence: 99%
“…Relative lack of depth perception (2D view) has been a major disadvantage with laparoscopy compared to open surgery. To overcome this, 4K ultra high definition technology[ 35 ] and 3D laparoscopic technology have been introduced[ 36 ], and several trials have compared the two[ 35 , 37 ]. Neither seems superior to the other, and a recent consensus statement from the European Association of Endoscopic Surgeons concluded that further robust research is required to investigate the avantages of 3D laparoscopy system[ 38 ].…”
Section: Peri-operative Considerationsmentioning
confidence: 99%
“…Technological innovations in optics and robotics help to support and improve the surgeon’s eyes and hands, and yet adverse surgical events remain an unsolved problem 1 3 . According to a report on human performance errors during surgery, nearly 30% of surgical complications are caused by misrecognition (MR) during operations 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding operation needs, it has been shown that 4 K ultra HD monitors reduce operative time and intraoperative blood loss in colorectal laparoscopic surgery, so these technologies with higher quality should be widely incorporated in clinical settings for the normal colonoscopy practices, since currently these 4 K ultra HD technologies are mainly available in specialized, high-volume laparoscopic centers [ 79 ]. However, the reduction of operative time achieved with these technologies should be taken with caution, as acting quickly with a shorter withdrawal time is also associated with higher interval CRC rates [ 80 ].…”
Section: Discussionmentioning
confidence: 99%